2010
DOI: 10.1590/s0001-37652010000100012
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial testing of canine annulus fibrosus tissue under changing salt concentrations

Abstract: The in vivo mechanics of the annulus fibrosus of the intervertebral disc is one of biaxial rather than uniaxial loading. The material properties of the annulus are intimately linked to the osmolarity in the tissue. This paper presents biaxial relaxation experiments of canine annulus fibrosus tissue under stepwise changes of external salt concentration. The force tracings show that stresses are strongly dependent on time, salt concentration and orientation. The force tracing signature of a response to a change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The swelling properties of tissues can be quantified by measuring hydration, osmotic swelling, and creep behavior in baths having differing osmolarity. 4,6,19,47,48 Disk degeneration is associated with loss of proteoglycans and decrease in pH that both reduce the fixed charge density (FCD). 16,39,48 …”
Section: Introductionmentioning
confidence: 99%
“…The swelling properties of tissues can be quantified by measuring hydration, osmotic swelling, and creep behavior in baths having differing osmolarity. 4,6,19,47,48 Disk degeneration is associated with loss of proteoglycans and decrease in pH that both reduce the fixed charge density (FCD). 16,39,48 …”
Section: Introductionmentioning
confidence: 99%
“…N um erous studies have reported the A F com pressive [9][10][11][12][13] and tensile properties, 11, 14-17 but specific conditions required to determ ine m odelparam eters for the osm oviscoelasticm odelare unavailable.In com pression, previous studies quantified the load distribution and shiftbetw een fibrillarand solid m atri cesin the annulus.…”
mentioning
confidence: 99%
“…Keeping bone is a solution 3 but limited by bone brittleness and potential bone failure during cutting and grips pressure. The annulus specimens may be also glued with cyanoacrylate to grips, [26][27][28] the cyanoacrylate stiffness being much higher than the annulus stiffness (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) and its influence may be neglected. Here, the specimens were glued at metal plates using cyanoacrylate and then immerged in a 9-g/ L saline solution during 100 min to reach equilibrium swelling and to cancel all residual stresses due to specimen preparation.…”
Section: Specimen Preparationmentioning
confidence: 99%
“…The underlying coupling depends on the chemical state of the disc 20 with variations in fluid content inside extracellular matrix and modifications in chemical equilibrium. 10,[21][22][23][24] Although inelastic and osmotic effects in the disc usually appear together, the coupling between both effects is rarely studied. 1,[8][9][10]20,25 The evaluation of the intrinsic annulus mechanics including multiple lamellae in relation with the surrounding chemical environment should bring precious information on the implication of proteoglycans/collagen fibers as well as inter-lamellae interactions on the coupling between osmotic and inelastic effects (the interaction between inelastic effects and osmolarity effects will be termed as osmo-inelastic coupling).…”
Section: Introductionmentioning
confidence: 99%